Kesenian Rapa’i Bubee: Realisme Magis dalam Seni Tradisi Masyarakat Pidie Jaya - Tria Ocktarizka; Rizki Mona Dwi Putra; Erlinda (Grenek: Jurnal Seni Musik, 2026)
Rapa'i Bubee is a traditional art form from Meureudu, Pidie Jaya Regency, which represents an oral narrative about the efforts of religious scholars to conquer Jin Pari through rapa'i percussion and traditional media such as aree, jeuee, and bubee. This study aims to describe the transformation of function, structure, and mystical meaning in the Rapa'i Bubee performance. The study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation studies. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions. The results show that Rapa'i Bubee has undergone a transformation from a supernatural healing ritual to entertainment and a medium for historical education. Elements considered contrary to Islamic teachings, such as the burning of incense, have been removed without losing the cultural identity of the performance. Despite the change in function, the magical dimension is still apparent through the phenomenon of trance of the performers who are controlled by the Caliph through the regulation of the tempo of the percussion as a symbol of the conquest of astral beings.